Inventarisasi Capung (Odonata) di Sekitar Sungai dan Rawa Moramo, Desa Sumber Sari Kecamatan Moramo Kabupaten Konawe Selatan Sulawesi Tenggara (Dragonfly (Odonata) Stocktaking Around River and Moramo Swamp, Sumber Sari Village, Moramo District, South Ko - ., Suriana; Adi, Dwi Arinto; Hardiyanti, Wa Ode Dian (Jurnal BioWallacea, 2014)
The aim of this research was to know the dragonfly (Odonata) spesies around River and Moramo Swamp, Sumber Sari Village, Moramo District, South Konawe Regency, South-East Sulawesi. Dragonfly captured on three site namely river, swamp I and swamp II/ Moramo swamp. This research used descriptive method. There are 28 species of dragonfly which are include of 8 family namely Lindeniidae, Libellulidae, Megapodagrionidae, Lestidae, Coenagrionidae, Calopterygidae, Chlorocyphidae and Plactynemididae. Suborder Epiprocta found 13,33% family and 50% suborder Zygoptera of all families. There are 12 species in river, 15 species in swamp I and 13 species in swamp II/Moramo swamp. The Calopterygidae, Megapodagrionidae and Platycnemididae only found in river, whereas Lestidae (Lestes concinus Hagen) found in swamp only. The dragonfly spesies found in river were diffirent from swamp I and swamp II/Moramo swamp. Â Key word:Â Dragonfly, Odonata, Moramo Swamp, River,Stocktaking